Pengaruh Pemasaran, Media Sosial, dan Kepercayaan Merek terhadap Repurchase Intention Semarang - Dedy Gigih; Asyhari Asyhari (Penerbit Goodwood, 2025)
Purpose: This research aims to examine the impact of experiential marketing, social media marketing, and brand trust on repurchase intention, with customer satisfaction acting as an intervening variable, within the context of Umrah travel agencies in Semarang City. Methodology/approach: A quantitative explanatory research design was employed, involving 100 respondents who had used Umrah travel services at least twice in the last five years. Data were collected via questionnaires and analyzed using SmartPLS software. Results/findings: The results indicate that experiential marketing, social media marketing, and brand trust have a significant impact on customer satisfaction, which subsequently exerts a positive influence on repurchase intention. Customer satisfaction acts as a crucial mediating variable in these relationships. Conclusion: The study concludes that experiential marketing, social media marketing, and brand trust have a positive and significant effect on customer satisfaction, which in turn increases repurchase intention. Among these factors, experiential marketing has the strongest influence, making its implementation highly effective in driving customer satisfaction and loyalty in Umrah travel agencies. Limitations: The study is limited to a relatively small sample size and specific Umrah travel agencies in Semarang, thus limiting the generalizability of the findings. Contribution: This research contributes to marketing strategies by emphasizing the pivotal role of customer satisfaction in mediating the relationship between key marketing factors and repurchase intention. It offers practical insights for Umrah travel agencies to strengthen customer loyalty and gain a competitive edge.